Do Swiss foreign assets hedge the business cycle? - Nicolas Stoffels; Cédric Tille (Aussenwirtschaft, 2018)
While Switzerland's net creditor position is sizable, it has long remained steady despite large and persistent current account surpluses. This pattern reflects valuation losses on Swiss foreign assets driven by movements in exchange rates and assets prices. We compute estimates of these valuation effects and the associated rates of returns on Swiss external assets and liabilities. While Switzerland benefits from a modest advantage in terms of yields (interest and dividends in percent of holdings), we show that this has been dwarfed by valuation losses driven by the strengthening of the Swiss franc, even before the crisis. We then assess the extent to which the return on assets and liabilities (including capital gains) provides a hedge against movements in Swiss GDP and the purchasing power of income. While we find little evidence of such a hedge at a quarterly frequency, financial returns provide some offset for business cycle movements at the horizon of a year. This hedging property has strengthened since 2010 and is more pronounced for privately held assets and liabilities than for the fast-growing holdings of reserves by the Swiss National Bank.
Keywords: G15; F21; F31; F36; F44; F65; 330; valuation effects; international risk sharing